Effect of Cyclic Loading on Polyethylene Netting Yarn - M., Mukundan; M., Shahul Hameed (Fishery Technology, 2025)
Polyethylene netting yam (0.75 nun nominal dia) was subjected to repeated stressing for 10, 20, 30 and 60 cycles under different loads of 5, 10 and 20 g texÂ·’ and the remaining elongation assessed after relaxation periods of 0, 2, 24 and 48 h. Elongation for maximum load and for two intermediate values of load (37 and 74 N) were recorded. The elongation values with respect to particular load remained almost the same in tests with 5 g texÂ·t load. Strained specimens under all stages never reached the original value of breaking load. Statistical analysis to ascertain causative factors indicates the dependence of the amount of loading on elongation but not the other factors like number of cycles or relaxation time.